Do tuition increases lower student academic performance?. (2016) - Mujumdar, Sudesh; Friesner, Daniel; Schibik, Timothy; Harrington, Charles
In this paper, we develop and test an economic model which examines the relationship between changing (usually increasing) college tuition and students' academic performance, with specific attention paid to intermediate role played by the financing of a student's education. To do so, we extend Mujumdar, et al.'s (2004) tuition-performance trade-off model to allow for the inclusion of student loans and heterogeneity in family support for college. Predictions from the model are tested using a panel of students drawn from a Midwestern, regional public institution between 1998 and 2005. The results indicate that a one-unit increase in a student's overall financial burden reduces her/his grade point average by approximately 0.22 units in any given semester and her/his cumulative grade point average by 0.20 units. Consequently, colleges that have consistently increased education costs over this time frame may have indirectly harmed the welfare of their students.